PROCESO DIDÁCTICO DEL DOCENTE EN AMBIENTES DE APRENDIZAJE CLÍNICO - ODONTOLÓGICOS - Álvarez Montero, Carmen Julia; Rojas de Morales, Thaís; Navas, Rita; Quero Virla, Milton (Acta Odontológica Venezolana, 2013)
This work had as objective to analyze the pedagogic practice of the teacher in environments of clinicaldental learning. Methodology: It was carried out an observational descriptive study that considered the 28 teachers that are in charge of the fourth year students of the career assigned to private hospitals within the city of the Faculty of Dentistry of Zulia´s University; an observation guide was used directed toward the frequency of pedagogic behaviors, discriminated in six analysis categories and 24 items. A descriptive statistical analysis of the items was carried out, based on absolute and percent absolute and relative frequencies, the calculation of averages and standard deviations to allow qualifying each category according to the valuation scale "Non appropriate", "Appropriate" and "Very Appropriate". Results: the categories of analysis Explanation and orientation of the objectives, Use of teaching means and Methodological treatment, they could be qualified as "appropriate"; the Organization Form of the practical session and the Interpersonal Relationships with the students were qualified as "very appropriate". An atypical behavior regarding the rest of the categories was reflected in the category Learning Evaluation, qualifying as "not appropriate", it indicates that there are aspects in which is necessary to work for improving. Resumen Este trabajo tuvo como objetivo analizar la práctica pedagógica del docente en ambientes de aprendizaje clínico-odontológicos. Metodología: Se realizó un estudio descriptivo observacional que consideró los 28 docentes que tienen a su cargo alumnos del cuarto año de la carrera asignados en las clínicas intramuros de la Facultad de Odontología de la Universidad del Zulia; se empleó una guía de observación dirigida hacia la frecuencia de comportamientos pedagógicos, discriminada en seis categorías de análisis y 24 ítems. Se realizó un análisis estadístico descriptivo de los ítems, basado sobre frecuencias absolutas y relativas porcentuales, el cálculo de promedios y desviaciones estándar para permitir calificar cada categoría según la escala de valoración "No adecuada", "Adecuada" y "Muy Adecuada". Resultados: las categorías de análisis Explicación y orientación de los objetivos, Utilización de medios de enseñanza y Tratamiento metodológico, pudieron ser calificadas como "adecuadas"; la Forma de organización de la sesión práctica y las Relaciones interpersonales con los alumnos se calificaron como "muy adecuadas". Un comportamiento atípico respecto al resto de las categorías se reflejó en la categoría Evaluación del aprendizaje, calificándose como "no adecuada", lo que indica que hay aspectos en los que hay que trabajar para mejorar.